2021
DOI: 10.3389/fneur.2021.651096
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Microgliosis With the Colony-Stimulating Factor 1 Receptor Inhibitor PLX3397 Does Not Attenuate Memory Defects During Epileptogenesis in the Rat

Abstract: Events of status epilepticus (SE) trigger the development of temporal lobe epilepsy (TLE), a type of focal epilepsy that is commonly drug-resistant and is highly comorbid with cognitive deficits. While SE-induced hippocampal injury, accompanied by gliosis and neuronal loss, typically disrupts cognitive functions resulting in memory defects, it is not definitively known how. Our previous studies revealed extensive hippocampal microgliosis that peaked between 2 and 3 weeks after SE and paralleled the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Microglia depletion, either by hippocampal clodronate infusion or PLX3397 (1 week), had a transitory negative effect on BM acquisition, not evident after 3 weeks of depletion (Torres et al, 2016). Accordingly, 2-3-weeks of PLX did not affect spatial learning and memory in young mice (Elmore et al, 2014;Dagher et al, 2015;Willis et al, 2020) and rats (Wyatt-Johnson et al, 2021). A noticeable exception was found in aged mice, where PLX5622 (3 weeks) impaired memory retention especially in females (Unger et al, 2018).…”
Section: Spatial Learning and Memorymentioning
confidence: 81%
See 2 more Smart Citations
“…Microglia depletion, either by hippocampal clodronate infusion or PLX3397 (1 week), had a transitory negative effect on BM acquisition, not evident after 3 weeks of depletion (Torres et al, 2016). Accordingly, 2-3-weeks of PLX did not affect spatial learning and memory in young mice (Elmore et al, 2014;Dagher et al, 2015;Willis et al, 2020) and rats (Wyatt-Johnson et al, 2021). A noticeable exception was found in aged mice, where PLX5622 (3 weeks) impaired memory retention especially in females (Unger et al, 2018).…”
Section: Spatial Learning and Memorymentioning
confidence: 81%
“…In contrast, in adult animals a large set of studies consistently found no effect of microglia depletion, either pharmacological or genetic, in recognition memory in the NOR and NOL tasks (Acharya et al, 2016;Feng et al, 2016;Gibson et al, 2019;Kakae et al, 2019;Allen et al, 2020;Crapser et al, 2020;De Luca et al, 2020;Worthen et al, 2020;Witcher et al, 2021;Wyatt-Johnson et al, 2021). No effects have been observed upon microglia repopulation either (Elmore et al, 2015;De Luca et al, 2020;Henry et al, 2020).…”
Section: Object and Location Recognition Learning And Memorymentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, duration of microglia eradication in other diseases led to various outcomes. A 3-week PLX3397-treatment in a mouse model of temporal lobe epilepsy had no effect on memory deficits [ 30 ], whereas a 3-month treatment in a mouse model of Alzheimer’s disease reduced amyloid plaque formation [ 31 ]. Differences in the functional outcome observed after a complete or selective subset of microglia depletion in neurological diseases and trauma may also reflect a molecular and functional heterogeneity of microglia and their responses, depending on the location in the CNS (for review see [ 32 ]), as well as the type of damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that suggests the opposite, emphasizing the neuroprotective role of CSF-1/CSF-1R. CSF-1R inhibitor PLX3397 has been reported to significantly reduce the number of microglia which resulted in exacerbated brain infarction and vividly increased the production of inflammatory mediators by astrocytes [ 177 , 178 ] (Fig. 4 ) (Table 4 ).…”
Section: Colony-stimulating Factor-1 and Macrophage Differentiationmentioning
confidence: 99%